Expanded expression of pro-neurogenic factor SoxB1 during larval development of gastropod Lymnaea stagnalis suggests preadaptation to prolonged neurogenesis in Mollusca - Kurtova, Anastasia I.; Finoshin, Alexander D.; Aparina, Margarita S.; Gazizova, Guzel R.; Kozlova, Olga S.; Voronova, Svetlana N.; Shagimardanova, Elena I.; Ivashkin, Evgeny G.; Voronezhskaya, Elena E. (Frontiers in Neuroscience, 2024)
The diversity in the organization of the nervous system in mollusks raises intriguing questions about its development and evolution. Our study aims to gain a deeper understanding of how the nervous system forms in Mollusca by examining the involvement of SoxB-family transcription factors in the early development of neurogenic zones. Specifically, we explore the expression patterns of two SoxB genes in the gastropod Lymnaea stagnalis, namely LsSoxB1 and LsSoxB2, across various developmental stages. Through a combination of in situ hybridization chain reaction, immunohistochemistry, and proliferation assays, we examine the dynamic spatial distribution of LsSoxB1 and LsSoxB2, with a particular emphasis on the formation of central ring ganglia and the identification of active proliferative zones. Our findings reveal that LsSoxB1 exhibits expanded ectodermal expression from the gastrula to the postmetamorphic stage, evident at both transcriptional and translational levels. Throughout larval development, LsSoxB1 is expressed in the ectoderm of the head, foot, and visceral complex, as well as in forming ganglia and sensory cells. In contrast, the expression of LsSoxB2 in the ectoderm is observed until the veliger stage, after which it persists in subepithelial layer cells and within forming ganglia. Proliferation assay reveals a uniform distribution of dividing cells in the ectoderm at all developmental stages, indicating the absence of distinct neurogenic zones with increased proliferation in gastropods. Our findings highlight that LsSoxB exhibit widespread expression patterns in both location and time compared to other Lophotrochozoa species. This prolonged expression of SoxB genes in gastropods can be interpreted as a form of transcriptional neoteny, playing a crucial role in the diversification of nervous systems. Thus, it serves as a preadaptation to prolonged neurogenesis and an increase in the central nervous system complexity in Mollusca.